Optimisation of suspended-deck bridge design: a case study. Issue 3 (2nd July 2020) - Mascolo, Ida; Modano, Mariano
ABSTRACT: The study deals with the optimum suspended-deck bridge (i.e. suspension, cable-stayed and tied-arch bridges) design through cable adjustment. An easy linear analysis procedure is proposed based on the Force Equilibrium Method. It includes a preliminary identification of the objective function through a mathematical Sensitivity Analysis (SA) and an optimisation procedure based on the Influence Matrix Method (IMM). It neglects time-dependent effects and geometric nonlinearities. In spite of its simplicity, the proposed approach has proven to be good and functional and, on account of its straightforward physical meaning, also suitable to practising engineers. It aims to obtain an optimal moment distribution on the deck with a reasonable increment in the cable forces. An optimal distribution of stress in the cables can also be pursued. The proposed procedure is rather general and can be applied to both the design and the construction stages. The Gravina Bridge in Matera, Italy, is used as a model to illustrate the method and its applicability to practical engineering problems.